On the origin of mongrels: evolutionary history of free-breeding dogs in Eurasia - Malgorzata Pilot; Tadeusz Malewski; Osama Mohammed; Grzegorz Klys; Innokentiy Okhlopkov; Ewa Suchecka; Wieslaw Bogdanowicz; Andre Moura; Tomasz Grzybowski; Kamil Olenski; Anna Rusc; Stanislaw Kaminski; et al. (2015)
Although a large part of the global domestic dog population is free-ranging and free-breeding, knowledge of genetic diversity in these free-breeding dogs (FBDs) and theirancestry relations to pure-breed dogs is limited, and indigenous status of FBDs in Asia isuncertain. We analyse genome-wide SNP variability of FBDs across Eurasia, and showthat they display weak genetic structure, and are genetically distinct from pure-breeddogs rather than constituting an admixture of breeds. Our results suggest that modernEuropean breeds originated locally from European FBDs. East Asian and Arctic breedsshow closest affinity to East Asian FBDs, and they both represent earliest-branchinglineages in the phylogeny of extant Eurasian dogs. Our biogeographic reconstruction ofancestral distributions indicates a gradual westward expansion of East Asian indigenousdogs to the Middle East and Europe through Central and West Asia, providing evidencefor a major expansion that shaped the patterns of genetic differentiation in moderndogs. This expansion was probably secondary and could have led to the replacement ofearlier resident populations in Western Eurasia. This could explain why earlier studiesbased on modern DNA suggest East Asia as the region of dog origin, while ancient DNAand archaeological data point to Western Eurasia.